Phase Manifestation and Formation of Nanoemulsions Composed of Imidazolium-based Ionic Liquid, Tween 80/Span 80 and Labrafac Lipophile WL 1349 - S. H. Ng; P. M. WOI; C. C. ENG (ASEAN Journal on Science and Technology for Development, 2015)
onic liquids (ILs) can enhance topical and transdermal delivery, as well as increase the solubility of sparingly soluble drugs. In the present work, pseudo-ternary phase diagrams of emulsions were composed of a mixture of non-ionic surfactants, polyoxyethylene sorbitan monooleate (Tween 80®) and sorbitan monooleate (Span 80®) in weight fraction: 1:1, 1:2, 2:1 and 2:3, LabrafacTM Lipophile WL 1349 as an oil phase and 1-hexyl-3-methylimidazolium chloride [(HMIM) (Cl)] as a continuous phase. Emulsion formulations were selected with 10% surfactants from the pseudo-ternary phase diagrams and further prepared at 298.2 ± 0.1 K. Acoustic emulsificationmethod was used to prepare nanoemulsions that were mixed with freshly prepared hydrocolloid gum. The area of the single-phase zone in pseudo-ternary phase diagrams that varied with Tween 80® /Span 80® ratio in the order of 2:1 > 1:1 > 2:3 > 1:2 where Span 80® was replaced by an equivalent weight of Tween 80®  to form IL-based nanoemulsions. [HMIM] [Cl] tended to create a two-phase system. Addition of carbopol® ultrez 20 copolymer into the continuous phase of the formulations gave single-phase nanoemulsions with good stability. The mixture of surfactants with weight ratio of 1:2 (Tween 80®/Span 80®) showed a good stability with the smallest particle size and greater surface charges in the system. These ionic liquid-based nanoemulsions might have the potential in drug delivery systems.